Automatic implantable cardioverter/defibrillator: inadvertent discharges during permanent pacemaker magnet tests. - Kim SG; Furman S; Matos JA; Waspe LE; Brodman R; Fisher JD (Pacing & Clinical Electrophysiology, 1987)
A patient with an automatic impIantable cardioverter defibrillator (AICD)(R) received two inadvertent shacks when a magnet was placed over the pacer during a routine permanent pacer check. Analysis of the rhythm strip suggested that both patients' QRS complexes (133 beats/minute) and asynchronous pacer artifacts (70 beats/minute) were counted by the AICD sensing system and exceeded the rate criteria of 153 beats/minute. This resulted in shocks from the AICD during sinus rhythm at 133 beats/minute. To avoid possible inadvertent shocks, an AICD should be deactivated while a magnet is placed over the pacemaker during a permanent pacer check.